Additive Manufacturing for Electrochemical (Micro)Fluidic Platforms. (January 2016) - Channon, Robert B.; Joseph, Maxim B.; Macpherson, Julie V.
Abstract : The ability to make electrochemical measurements under controlled fluid flow has many applications in electrochemical analysis, especially at trace levels. With a move to rapid, on-line, small volume measurements and a need to improve measurement performance, there is a requirement to manufacture more complex fluidic systems with controlled internal 3D geometries at low cost. Both precision machining and lithography typically fail to meet these needs. In this article we describe the role of additive manufacturing (AM) for the fabrication of (micro)fluidic electrochemical flow systems. We show how AM has advanced device manufacture in these areas compared to the more traditional approaches. Different AM methods are also discussed with respect to their capabilities and advantages. A selection of current AM electrochemical flow cell applications are highlighted and future perspectives discussed.